1989
DOI: 10.1016/0014-5793(89)80974-3
|View full text |Cite
|
Sign up to set email alerts
|

Probing the nucleotide‐binding site of sarcoplasmic reticulum (Ca2+‐Mg2+)‐ATPase with anti‐fluorescein antibodies

Abstract: Antibodies raised against fluoresccin were unable to bind to the fluorophore when bound at the nucleotide-binding site of native (Ca2+-Mg2+)-ATPase, as judged by fluorescence quenching assays or competitive ELISAs, but were able to bind when the ATPase was denatured. Indirect ELISAs, in which native and denatured FITC-ATPase were used to coat ELISA plates, were unable to detect the difference in accessibility of the fluorescein bound to the native and denatured ATPase. These results indicate that the nuclcotid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

1990
1990
1998
1998

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
2
5
0
Order By: Relevance
“…These results suggest the environment of bound FITC in p29/30 fragments produced by proteinase K treatment is somewhat different from its environment in intact Ca 2ϩ -ATPase but is not changed to the extent that it would become completely exposed to the aqueous medium. This conclusion is strengthened by experiments in which solvent accessibility of FITC is examined with the quenching agent iodide (see inset to (36), FITC accessibility to iodide is higher for free FITC than for FITC bound to Ca 2ϩ -ATPase (slopes for Stern-Volmer plots are 6.5 M Ϫ1 and 2.7 M Ϫ1 , respectively), suggesting restricted accessibility to FITC, a suggestion supported by immunoreactivity data (37). In p29/30 fragments, this accessibility has an intermediate value, close to that of FITC in intact Ca 2ϩ -ATPase (slopes for Stern-Volmer plots are 3.1 or 3.9 M Ϫ1 for supernatants after 15 or 45 min proteolysis, respectively; in the latter case, degradation of p29/30 fragments to much smaller peptides contributes to the larger slope).…”
Section: Soluble Domain Of Sarcoplasmic Reticulum Ca 2ϩ -Atpase 6627mentioning
confidence: 66%
“…These results suggest the environment of bound FITC in p29/30 fragments produced by proteinase K treatment is somewhat different from its environment in intact Ca 2ϩ -ATPase but is not changed to the extent that it would become completely exposed to the aqueous medium. This conclusion is strengthened by experiments in which solvent accessibility of FITC is examined with the quenching agent iodide (see inset to (36), FITC accessibility to iodide is higher for free FITC than for FITC bound to Ca 2ϩ -ATPase (slopes for Stern-Volmer plots are 6.5 M Ϫ1 and 2.7 M Ϫ1 , respectively), suggesting restricted accessibility to FITC, a suggestion supported by immunoreactivity data (37). In p29/30 fragments, this accessibility has an intermediate value, close to that of FITC in intact Ca 2ϩ -ATPase (slopes for Stern-Volmer plots are 3.1 or 3.9 M Ϫ1 for supernatants after 15 or 45 min proteolysis, respectively; in the latter case, degradation of p29/30 fragments to much smaller peptides contributes to the larger slope).…”
Section: Soluble Domain Of Sarcoplasmic Reticulum Ca 2ϩ -Atpase 6627mentioning
confidence: 66%
“…2. It has been shown that antibodies to fluorescein bind to denatured FITC-labelled ATPase, but not to native FITC-labelled ATPase, consistent with a location for the fluorescein in a hydrophobic cleft between the phosphorylation and nucleotide-binding domains (Mata et al, 1989). Surface exposure of residues 510-515 would be inconsistent with their forming a fl-sheet structure in the binding cleft for ATP, as suggested by Taylor & Green (1989).…”
Section: Discussionmentioning
confidence: 87%
“…In order to explain this result, it should be mentioned that the highly immunogenic region of the Ca2+-ATPase molecule is located near the ATPbinding site, where binding of antibodies is severely limited [32]. The Triton X-100 treatment given to the immunofluorescence sections might facilitate the access of the antibodies and thus justify the strong signal observed.…”
Section: Discussionmentioning
confidence: 99%
“…It has been calculated that at physiological pH the E1/E2 ratio for rabbit skeletal-muscle SR Ca2+-ATPase is 0.5 [35]. Since vanadate binds to the E2 form [32], it may be suggested that the difference in vanadate-sensitivity reflects, at least in part, a difference in this ratio, with the nonmuscle enzyme equilibrium displaced towards the E2 form. From these data we conclude that the cerebellar, the skeletal muscle and the heart SR Ca2+-ATPase, in spite of their similar molecular masses and of the shared immunological determinants, are distinct molecular isoforms.…”
Section: Discussionmentioning
confidence: 99%